Analisis Kebijakan Hukum Pidana dalam Pasal 45 Ayat (4) Jo. Pasal 27 Ayat (4) UU ITE - Muhammad Al Riyadh; Sigid Suseno; Rully Herdita Ramadhani (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2024)
Law no. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) regulates criminal acts of extortion and threats in one article formulation, namely Article 45 paragraph (4) jo. Article 27 paragraph (4). These two criminal acts have different qualifications for offenses as formulated in the Criminal Code and are rubber articles so that in their application they cause many victims, as in several decisions, namely Decision Number 111/Pid.Sus/2021/PN Ptk, Decision number 130/Pid. Sus/2018/PN Jkt Utr, and Decision number 777/Pid.Sus/2019/PN Jkt Pst. Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 concerning Electronic Information and Transactions, the new ITE Law, has amended the previous amendment which changed the rubber article formulating the criminal offenses of extortion and threats which were separated into different article formulations. The author uses a normative research model sourced from library materials with a legal and conceptual approach. This research concludes that combining two criminal acts in one article formulation can lead to errors in interpretation or understanding by law enforcers of Article 45 paragraph (4) jo. Article 27 paragraph (4) of the ITE Law is old so there is the potential for human rights violations. This error in application occurs when the provisions for the offense of making complaints against suspects of criminal threats are not enforced